Outcomes of pregnancy in neuromyelitis optica patients: turkish multicenter study data - Altintas, A.; Uygunoglu, U.; Terzi, M.; Boz, C.; Saip, S.; Koseoglu, M.; Siva, A. (Sage Publications Ltd, 2016)
[Abstract Not Available]
32nd Congress of the European-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ECTRIMS) -- SEP 14-17, 2016 -- London, ENGLAND